Evaluation of the Effect of Macronutrients Combination on Blood Sugar Levels in Healthy Individuals - Berrak BASTURK; Zeynep KOC OZERSON; Aysun YUKSEL (Tehran University of Medical Sciences, 2021)
Background: The positive effects of blood glucose levels should be demonstrated in healthy or type 2 diabetic individuals who can be recommended to consume macronutrients (protein + fat) with carbohydrates. Therefore, at the end of the research planned with the amount of carbohydrates and fats that can be consumed in a meal, we aimed to recommend the consumption of food with high protein content egg together with the carbohydrate source. Methods: The study was carried out from Nov 2017 to Apr 2018 by looking at fasting blood glucose levels using feeding 2 different test foods on a minimum of 8 h of fasting in the Haliç University Sutluce Campus, Istanbul, Turkey. Before and after the carbohydrate and carbohydrate + protein source, blood glucose was measured from the fingertip for 3 days in 30 min, 60 min and 120 min periods. The average of 3 days was used in the analysis. Results: Blood glucose values were compared after individuals were given carbohydrate and carbohydrate + protein source. The mean blood glucose value 60 min after the carbohydrate administration was significantly higher than the average blood glucose value 60 min after the carbohydrate + protein administration (P= 0.006 Conclusion:  A protein-containing diet positively affects the glycemia response and can recommend it. In individuals with diabetes, they should focus on the effects of proteins to achieve glycemia control.